OĞUZ ATAY’IN “TAHTA AT” HİKÂYESİ ÜZERİNE BİR İÇERİK İNCELEMESİ - (:unkn) unknown (My University, 2015)
Kullandığı yeni anlatım tarzı, üslûbu ve işlediği konularla Türk Edebiyatına yeni bir soluk getiren Oğuz Atay, romancılığı ile olduğu kadar hikâyeciliği ile de dikkat çeker. Bütün hikâyelerini Korkuyu Beklerken ( 1975) adlı kitabında bir araya getiren yazar, burada yer alan sekiz hikâyesinde hem muhteva-konu hem de biçim-anlatım tekniği itibariyle mühim örnekler sunar. Bu kitapta bulunan "Tahta At" hikâyesi, hem zengin konu arka planı hem de büyük ölçüde ironiye dayanan anlatım şekli ile tıpkı diğer hikâyeler gibi tahlile değer bir nitelik ve mahiyet taşımaktadır. Hikâyenin bütününde Cumhuriyet Dönemi estetik anlayışı, mimarî üslûpsuzluklar, bilinçsiz şehir-kasaba düzenlemeleri alaycı bir dille tenkit edilir. Ayrıca yine bu dönem içerisinde var olan çıkarcı, cahil, ukala ve fikrî manada deforme olmuş insanlar ortaya koyulur. Yazar, dönemin panoramasını bir taşra kasabası üzerinden ayrıntıları gösterip problemleri irdelemek suretiyle vermeye gayret eder. Bu incelemede söz konusu hikâye, hikâyenin aslî şahsı olan Tuğrul Bey merkeze alınarak, başta içerik ve konu arka planı cihetiyle olmak üzere tahlil edilip değerlendirilmeye ve yorumlanmaya çalışıldı. İncelemenin bütününde değerlendirmeler yapılırken olay örgüsünün ilerleyişi takip edildi ve gerekli görülen kısımlarda kurguyu çözümlemeye yönelik okur merkezli yorum ve açıklamalarda bulunuldu. Ayrıca ortaya koyulan düşünceleri ve ileri sürülen görüşleri daha somut bir şekilde yansıtabilmek adına sık sık hikâyeden örneklere/alıntılara yer verildi

Oğuz Atay who brought a breath of fresh air to Turkish literature with a new turn of phrase and his topics, draws attention with also his stories as well as his novels. The writer who brought together all his stories in Korkuyu Beklerken (1975) represents important examples in terms of content-topic and form-turn of phrase in these eight stories. "Tahta At" (Wooden Horse) is worth to analyze with its rich subject background and its turn of phrase which is based mainly on irony. "Tahta At" is based on the fictional narrative of modernized and cultural Trojan War enriched with symbolic expressions. In the whole story, social deformation which is a substantial problem of the country and the amorphous architectural-aesthetic perception of the Republican period and its application to the cities that was wanted to be modernized by imposing sactions is tried to be put forth in the frame of the struggle of protagonist Tuğrul and the Trojan horse that is wanted to be built on the ruins to make it a reminder of the historical significance. . In the story, sense of aesthetics of Republican period, architectural disharmony, senseless city planning are critisized cynically. In addition to that, manipulative, ignorant, know-it-all and intellectually deformed people of that period are put forward. The writer tries to represent the panorama of the period by showing the details of a country town and examining the problems. In this analysis, the story in question is tried to be evaluated and interpreted based on protagonist Tuğrul Bey in terms of content and subject background. While analyzing, the operation of the plot is followed and when it's seen necessary, reader oriented interpretation and explanations are made. Also, quotations/examples from the story are often used in order to reflect the ideas and opinions that are asserted more substantially. The plot of the story takes place in a linear timeline of a few weeks. Mostly, third person narrative is used and the protagonist Tuğrul is always the centre of the story. The narrator mentions the events and characters by following him and from his point of view. The reader witnesses that Tuğrul stands against the the statue both mentally and bodily and he acts on his beliefs that this is a lofty aim. Tuğrul achieves to disturb the authorities and dictative government agencies with his actions and contradictory movements. But it is also possible to say that the writer shapes the narration on Tuğrul's quick temper and the gradual changes on his attitude. Tuğrul's new attitudes also generates the invisible parts of the story. At the beginning of the story, Tuğrul considers this statue by making fun of the approach of the Turkish people and the formalities and the architectural disharmony of Republican period in his mind. In time, this ridicule transforms into rage. And rage urges the protagonist to take action. In consequence, the effects of this actions increase progressively and causes the authorities to take serious precautions. It would be fair to state that the protagonist of "Tahta At" is different from the protagonists of the other stories in an important aspect. While other protagonists are in a passive, obscure and strifeless relationship with themselves and the life style they are used to, the protagonist of "Tahta At", Tuğrul is a fighter who opposes to the deatg the ideas and the people that he doesn't believe. Him pointing his gun to the people who are in charge of the sculpture is an obvious proof of that. It's unknown whether he fired his gun and killed somebody or not and whether he succeeded or failed to withstand the authority he is in a struggle with. But, it's certain that Tuğrul never gave up on his fight and he never dreaded and he acted brave enough to risk his life and use a gun. The most important feature when whole story is considered is the usage of irony. This element which is encountered a lot in the fictional works of Oğuz Atay is at the forefront in the story "Tahta At" and it enriches the story's content. The irony dominates the entire story from its headline -The statue is not called Trojan Horse, it's called wooden horse. But is's not built from wood but from concrete and iron as the name suggests.- to the plot and the dialogues to the monologues and to the narration. The end of the story is based on a different ironical situation. The writer completes the fiction with a surprising ending. Because the reader saw the police moving Tuğrul away and removing him from the city before the incident. Tuğrul Bey who is supposed to be at another place gets out of the wooden horse gravely during the opening ceremony just as the Achaean warriors coming out of Trojan Horse surprisingly in the history and appears in front of the crowd with his gun
A CONTENT ANALYIS ON OĞUZ ATAY'S STORY "TAHTA AT"